Biomarcadores endoteliais e de coagulação em envenenamento botrópico - Santos, Ranieri Sales de Souza (2024)
Ophidian accidents are an underestimated public health concern worldwide. It affects around 5.4 million people, resulting in 1.8 to 2.7 million illnesses and approximately 81,410 to 137,880 deaths. Snakes from the Viperidae family are the ones of greatest medical interest in Brazil, causing botropic accidents. The genus Bothrops sp. is responsible for more than 70% of the cases of snakebite accidents reported annually in Brazil. This study investigated the association between coagulation disorders and endothelial dysfunction in patients after botropic envenomation, using the biomarkers angiopoietin-1, angiopoietin-2, syndecan-1, VCAM-1, IL-33 and VWF-A2. It was conducted as a prospective, single-center cohort study, analyzing three collections at different time intervals (0-8, 12-16 and 24-28 hours) from 34 patients admitted to an emergency department due to Bothrops erythromelas snake bites. The study was carried out with patients treated at CIATOX at the Instituto Doutor José Frota, a renowned hospital for emergency toxicology care in Fortaleza-CE. Poisoning occurred mainly in the male population, at an average age of 46.3 ± 14.5 years. Around 80% of the patients had blood incoagulability. In the first sampling, there were no differences in the parameters of platelets, leukocytes, hemoglobin, hematocrit, erythrocytes, glucose, sodium, potassium, calcium and chloride between the patients with and without bleeding. In the second sampling, a decrease in hematocrit and red blood cell count was observed in the patients with bleeding. In the third collection, patients with bleeding had lower hemoglobin, hematocrit and red blood cell counts compared to those without bleeding. Between 12 and 16 hours after the snakebite, patients who bled had higher serum levels of syndecan-1 and lower levels of IL-33 compared to those who did not bleed. These differences decreased 24 hours after the bite, with no significant differences in the non-conventional biomarkers VWFA2, syndecan-1 and IL-33. IL-33 showed an increase between the first and second sampling, but it was not significant. Von Willebrand factor showed a reduction followed by an increase between samples, which was not statistically significant, but indicated an initial drop followed by an attempt to normalize. The new biomolecules are important for diagnosing Bothrops erythromelas snake envenomation. The bleeding group showed significant levels of angiopoietin-1, angiopoietin-2, IL-33 and vWFA2 biomarkers, related to hemoglobin, hematocrit, erythrocyte and Bothrops venom-induced coagulopathy tests. Finally, the biomarkers angiopoietin-1, angiopoietin-2 and VWF-A2 have the potential to be used in the early diagnosis of coagulation alterations and could contribute to therapeutic and clinical interventions related to Bothrops erythromelas snake envenomation.